Analysis of lung cancer morbidity and mortality based on particle swarm optimization. (September 2020) - Li, Naiwei; Cheng, Ziyi; Woo, Youngmin; Ha, Jongmyung; Kim, Andre
Abstract: Based on the particle swarm algorithm to establish a mathematical model, this article counts the air quality index, tobacco sales, the number of cancer hospitals and the number of health personnel from 2008 to 2019, and quickly calculates the morbidity and mortality of lung cancer over the years, and uses statistics The relative error between the value and the calculated value is the evaluation standard. The result proves that the relative error between the calculated value and the statistical value of the morbidity and mortality of lung cancer is less than 10%, indicating that the calculation result of the particle swarm algorithm has good confidence.